Sociologia: Revista da Faculdade de Letras da Universidade do Porto : marcas e transformações de um agente de produção científica sociológica (1991-2020) - Oliveira, Maria João (2022)
This article analyses the main marks and transformations of Sociologia - journal of the Faculty of Arts and Humanities of the University of Porto, over its thirty years and fifty published issues. The data presented is of a descriptive nature and concerns the structural characteristics of the journal, its authors, and published texts. Through this case, it is intended to contribute, in the field of the sociology of science, to the understanding of the path of the production of sociological knowledge in Portugal.